Neuronutrition in depression and anxiety disorder (Research, Society and Development, 2021)
Anxiety and depression are diseases increasingly present today, considered the diseases of the century, drastically affect the quality of life of the population. Through neuronutrition it is possible to analyze eating habits and their relationship with our cognitive performance, analyzing from physiology, biochemistry and microbiota to the influence of nutrition directly on the development of these mental disorders. This study aimed to understand, through a literature review, the role of neuronutrition in depression and anxiety disorder. from data such as: PubMed, SCIELO, Academic Google and CAPES, from the following descriptors: diet, anxiety, depression, nutrients, omega 3, vitamin D, brain and intestine, vitamins and nervous system. Through the study, it was possible to analyze how nutrition influences both the prevention and control and alleviation of symptoms.